Peter Eisenman - Arie Graafland (Footprint)
For quite a while, Peter Eisenman’s dissertation lived the life of a mystery text. Many architectural theorists knew about it, but it was not published until 2006. The facsimile reprint by Lars Müller finally makes available the complete typographic script that Eisenman defended in August 1963 at the University of Cambridge.